2021
DOI: 10.1093/nar/gkab1170
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic bulge nucleotides in the KSHV PAN ENE triple helix provide a unique binding platform for small molecule ligands

Abstract: Cellular and virus-coded long non-coding (lnc) RNAs support multiple roles related to biological and pathological processes. Several lncRNAs sequester their 3′ termini to evade cellular degradation machinery, thereby supporting disease progression. An intramolecular triplex involving the lncRNA 3′ terminus, the element for nuclear expression (ENE), stabilizes RNA transcripts and promotes persistent function. Therefore, such ENE triplexes, as presented here in Kaposi's sarcoma-associated herpesvirus (KSHV) poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…Within the four-way junction, with no unpaired nucleotides and perfect cross-strand stacking of the P1 helix G10 with P4 helix G47 and P2 helix C11 with P3 helix C46, each set of these coaxial stacking forms almost a continuous A-form helix. As expected, the L2 loop closes the P2 helix and binds the Fab BL3-6, consistent with the Fab-loop interactions observed for other RNA-BL3-6 complex crystal structures 46 , 47 , 49 , 50 , 52 , 53 . Similarly, a trinucleotide loop L3 and a tetranucleotide loop L4 close the P3 and P4 helices, respectively.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Within the four-way junction, with no unpaired nucleotides and perfect cross-strand stacking of the P1 helix G10 with P4 helix G47 and P2 helix C11 with P3 helix C46, each set of these coaxial stacking forms almost a continuous A-form helix. As expected, the L2 loop closes the P2 helix and binds the Fab BL3-6, consistent with the Fab-loop interactions observed for other RNA-BL3-6 complex crystal structures 46 , 47 , 49 , 50 , 52 , 53 . Similarly, a trinucleotide loop L3 and a tetranucleotide loop L4 close the P3 and P4 helices, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Among others, Fab BL3-6 has been a very effective chaperone to crystallize and determine the high-resolution crystal structures of several RNA targets 46 , 47 , 49 , 50 , 52 , 53 . The Fab binds to a hairpin RNA with 5′-AAACA-3′ pentaloop sequence closed preferably by a G-C pair, which allows facile engineering of the epitope sequence into the target RNA 46 , 47 , 49 , 50 , 52 , 53 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the expression of NEAT1, especially NEAT1-2, was obviously induced from 12 to 36 hpi in both primary human and mouse monocytes and macrophages ( Figures 1E-ii,iii ). As a control, lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), the vital component for speckle structure in the nucleus that might participate in the viral life cycle ( Swain et al, 2021 ), was detected, and the data showed that MALAT1 expression increased from 0 to 24 hpi and then collapsed ( Figure 1F ). Intriguingly, the transcription level of NEAT1-2 seemed to persistently exhibit higher fold changes in macrophages than in monocytes ( Figure 1E-iii ), and macrophages maintained a relatively lower viral load of HTNV than their counterpart monocytes ( Figure 1G ).…”
Section: Resultsmentioning
confidence: 99%